STRATEGI PENGEMBANGAN USAHA BISNIS PANGAN LOKAL OLAHAN UBIKAYU DI KABUPATEN BANYUMAS - Pujiati Utami; Dumasari Dumasari (Universitas Muhammadiyah Purwokerto, 2014)
Local food processed products made from cassava in the Kalibogor and Sokaraja districts consist of three main products, namely getuk goreng, ceriping cassava and klanting. Getuk goreng business center is located in the district of Sokaraja, particularly in central and west Sokaraja. Pekaja village in the District of Kalibagor is also the center of cassava cultivation, and mostly the farmers in Pekaja are not only cultivating cassava but also processing it, especially klanting. While Wlahar village become a center of business ceriping or cassava chips to the scale house industry. SWOT analysis shows that the business of processed food made from cassava in Banyumas is profitable enough, so that it can optimally utilize its competitiveness advantages by taking over market share, for instance increasing sales volume, promoting products to several tourist destinations and other areas, participating in exhibitions of superior local products and so. Katakunci : cassava, local food processed, strategy